2015
DOI: 10.1016/j.bjhh.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia: survival analysis of patients at a university hospital of Paraná

Abstract: ObjectiveThe aim of this study was to analyze the prognostic factors correlated with survival of patients with acute myeloid leukemia at the Hospital de Clínicas, Universidade Federal do Paraná between 2003 and 2009, as well as to investigate the clinical and epidemiological profile.MethodsThe overall survival and disease-free survival were statistically evaluated using the Kaplan–Meier method, the log-rank test and multivariate evaluation by Cox regression analysis.ResultsThe study population was predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
15
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
9
15
2
7
Order By: Relevance
“…Our results proved that higher number of WBCs was significantly associated with shorter EFS and OS and this came in agreement with other studies [ 26 ]. This significant negative correlation between higher WBC counts and reduced OS and DFS could be explained partly by the fact that high WBC counts were associated with an increased risk of tumor lysis syndrome and leukostasis and both were considered oncologic emergencies and subsequently affected the prognosis of patients [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results proved that higher number of WBCs was significantly associated with shorter EFS and OS and this came in agreement with other studies [ 26 ]. This significant negative correlation between higher WBC counts and reduced OS and DFS could be explained partly by the fact that high WBC counts were associated with an increased risk of tumor lysis syndrome and leukostasis and both were considered oncologic emergencies and subsequently affected the prognosis of patients [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…The median age at diagnosis in Latin American countries or developing countries is very similar to ours. Brazil has reported a median age at diagnosis of 33-44 years [27,28], and for other low-middle-income countries such as India and Malaysia the median age of patients with AML has been observed to be 40 and 39 years, respectively [29,30]. The exact cause of this age difference is unclear.…”
Section: Acute Myelogenous Leukemiamentioning
confidence: 99%
“…11 t(8.21), inv (16), and t(16;16) stand for good cytogenetic risk characteristics. 7 In systemic reviews and meta-analyses, it was found that FLT3-ITD mutation is associated with poor prognosis, whereas NPMI1 and CEPBA mutations are associated with good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…15 In the study by Padilha et al, 40.8% of the cases were classified as intermediate cytogenetic risk group. 16 In our study, karyotype analyses of 57 patients based on classical cytogenetics were available. Normal karyotype was observed in 36 of 57 patients and abnormal karyotype was observed in 21 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation